Analisi Hubungan Indeks Dow Jones, Indeks Hang Seng, Indeks Nikkei, Indeks Straits Times Dengan Indeks Harga Saham Gabungan - Ary Satria Pamungkas (STAI Asy-Syukriyyah, 2010)
The aim of the present study was to investigate the relation between Dow Jones index, Hang Seng index, Nikkei index, Straits Times index and IHSG (the composite stock index of Indonesia Stock Exchange). Data were analyzed through use of correlation analysis. Results indicate that there is significant correlation analysis. Results indicate that there is significant correlation between dow jones index, Hang Seng index, Nikkei index, Straits Times index and IHSG. The Implications for future research are discussed.